A New Assessment of Hydrological Change in the Source Region of the Yellow River - Pan Wu; Sihai Liang; Xu-Sheng Wang; Yuqing Feng; Jeffrey M. McKenzie (Water, 2018)
Hydrological responses to climate change are a widely concerning question, particularly for the source region of the Yellow River (SRYR), which is sensitive to climate change and is widely underlain by frozen ground. In considering climate change impacts on catchment properties, the traditional separation approach based on the Budyko framework was modified to identify and quantify the climatic causes of discharge changes. On the basis of the decomposition method, the traditional separation method and the modified separation method were used to analyse the discharge change in the SRYR. Using the observed annual maximum frozen depth (MFD) to indicate the frozen ground level, the impacts of frozen-ground degradation on the discharge change were further considered using the modified separation method. Our results show that the traditional separation approach underestimated climate-induced discharge change; over the past half-century, the discharge change in the SRYR has been primarily controlled by climate change. Increasing air temperature is generally a negative force on discharge generation; however, it also causes frozen ground to degrade—a positive factor for discharge generation. Such conflicting effects enhance the uncertainty in assessments of hydrological responses to climate change in the sub-basins with widely distributed permafrost.